Implementasi Metode TOPSIS dalam Sistem Pendukung Keputusan Pemilihan Kedelai Terbaik untuk Produksi Tempe - Ika Ima Nissa; Widyawati Widyawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
One of the most significant foods for the people of Indonesia, tempeh is made mostly from soybeans. Soybean quality selection is still mostly done by hand, relying on eye inspection and the expertise of business actors. This may cause subjective evaluations, lengthy decision-making processes, and uneven outcomes. With the TOPSIS technique as its foundation, this project intends to construct a Decision Support System (DSS) for selecting high-quality soybeans. Color, texture, price, scent, and flavor are some of the evaluation criteria. Observations and interviews were conducted in Rumah Tempe A-Zaki Padang to gather data for the research. Ranking the options according to how close they were to the positive ideal solution and how far away from the negative ideal solution was done using the TOPSIS approach. In terms of preference values, the Green Soybean option came out on top with 0.9692, followed by Black Soybeans with 0.2335, Yellow Soybeans with 0.1516, and Brown Soybeans with 0.1181. Based on these outcomes, it seems that TOPSIS can indeed provide objective suggestions for soybean selection according to a number of different standards. Business players in the tempeh industry may benefit from this decision support system by using it to choose high-quality soybean raw materials more efficiently and accurately.